Tracking ∼200 years of water quality in Muskrat Lake, a eutrophic lake trout lake in Ontario (Canada) with cyanobacterial blooms. (2nd July 2020) - Simmatis, Brigitte; Nelligan, Clare; Rühland, Kathleen M.; Jeziorski, Adam; Castro, Victor; Paterson, Andrew M.; Smol, John P.
Abstract: Simmatis B, Nelligan C, Rühland KM, Jeziorski A, Castro V, Paterson AM, Smol JP. 2020. Tracking ∼200 years of water quality in Muskrat Lake, a eutrophic lake trout lake in Ontario (Canada) with cyanobacterial blooms. Lake Reserv Manage. 36:260–277. Muskrat Lake is a deep (64 m), eutrophic lake in southeastern Ontario, Canada, that supports a natural lake trout population. Frequent algal blooms and low deep-water dissolved oxygen concentrations have generated management concerns. Based on anecdotal reports, algal blooms first occurred in the 1920s. Concern regarding recreational activities has escalated since the early 1980s. Monitoring records for total phosphorus (TP) and dissolved oxygen concentrations are sparse, requiring paleolimnological methods to extend our knowledge of past lake conditions. We inferred trends in past whole-lake primary production using visual-range spectroscopy-inferred chlorophyll a, nutrients using diatom assemblage changes, and end-of-summer volume-weighted hypolimnetic oxygen concentrations (VWHO) using chironomids to assess environmental conditions in Muskrat Lake over the past ∼200 years. Diatom taxa indicative of mesotrophic conditions were present throughout the sedimentary record, which suggests that Muskrat Lake was moderately productive before European settlement, with conditions worsening somewhat after ca. 1920, following land clearance and agricultural development. Chironomid-inferred VWHO trends suggest that the hypolimnion was not naturally well oxygenated, but deep-water oxygen levels declined further after ca. 1900 following European settlement. After ca. 1990, changes in diatom assemblage composition were consistent with climate-mediated increases in thermal lake properties, which might have contributed to cyanobacterial dominance. Whole-lake primary production increased after ca. 1900 and peaked ca. 1960, remaining stable until ca. 2006, after which it declined. Overall, Muskrat Lake has been productive over the past ∼200 years, but the cumulative effects of changes in nutrient loading and mixing patterns should be considered in future management decisions.